Improving the regulatory framework in the natural gas sector in Brazil - Vitale, Cristiana (OECD Publishing, 2022)
This paper describes and analyses recent reforms in the natural gas market in Brazil aimed at fostering a more open, competitive, efficient, and flexible gas sector. This paper reviews the changes in the regulatory framework using two lenses: the reform process seen through a regulatory policy lens and the resulting regulatory framework using the OECD Product Market Regulation (PMR) indicator. The paper includes policies options to further improve the regulatory framework in the sector and reap the full range of benefits of the reforms
Keywords: Economics; Brazil